Beamforming for heterogeneous cloud radio access network - Jiakuo ZUO; Longxiang YANG; Nan BAO (Tongxin xuebao)
To overcome the problem that previous researches for heterogeneous cloud radio access network (H-CRAN) mainly focus on single macro cell,and only considered the intracell interference in the one macro cell,while the inter cell interferences among different macro cells are neglected,H-CRAN with multiple macro-cells was studied,and the objective was to maximize system sum-rate through jointly optimizing the beamforming vectors of macro base stations (MBS) and remote radio heads (RRH).Based on alternating optimization and Lagrangian dual method,a joint MBS and RRH beamforming algorithm was proposed.The original problem was first divided into two subproblems.Then,the two sub-problem were solved alternately to obtain the final solutions of the original problem.In addition,the closed expression solutions of the two sub-problem were derived based on Lagrangian dual method.The proposed algorithm was compared with some beamforming algorithms in the simulation.The experimental results demonstrate the proposed algorithm has a better performance in improving the sum-rate of H-CRAN.